Haem-dependent dimerization of PGRMC1/Sigma-2 receptor facilitates cancer proliferation and chemoresistance - Yasuaki Kabe (Nature Portfolio, 2016)
PGRMC1 binds to EGFR and cytochromes P450, and is known to be involved in cancer proliferation and in drug resistance. Here, the authors determine the structure of the cytosolic domain of PGRMC1, which forms a dimer via haem–haem stacking, and propose how this interaction could be involved in its function.